Experimental investigations of a highly maneuverable mobile omniwheel robot. (13th December 2017) - Kilin, A; Bozek, P; Karavaev, Yury; Klekovkin, A; Shestakov, V
In this article, a dynamical model for controlling an omniwheel mobile robot is presented. The proposed model is used to construct an algorithm for calculating control actions for trajectories characterizing the high maneuverability of the mobile robot. A description is given for a prototype of the highly maneuverable robot with four omniwheels, for which an algorithm for setting the coefficients of the PID controller is considered. Experiments on the motion of the robot were conducted at different angles, and the orientation of the platform was preserved. The experimental results are analyzed and statistically assessed.